간내 담관의 국소확장 형태로 나타난 점액 분비성 간내 담관암 - 김주동(Joo Dong Kim); 장혁재(Hyuk Jai Jang); 조용필(Yong pil Cho); 김용호(Yong Ho Kim); 정승문(Seung Mun Jung); 강길현(Kil Hyun Kang); 한명식(Myeng Sik Han) (Annals of surgical treatment and research, 2004)
A case of a mucin-producing intrahepatic cholangiocellular carcinoma (MPCC) is reported. A 58-year old female presented with epigastric discomfort of several years duration. The physical examination and laboratory findings were normal. Abdominal ultrasonography (US) and computed tomography (CT) showed a focal dilatation of the right posterior intrahepatic bile duct. There was no abnormal mass in the liver parenchyma. Endoscopic retrograde cholangiopancreaticography (ERCP) showed a filling defect in the right posterior hepatic duct. There was no anatomical abnormality and abnormal staining on the heaptic angiography. At the operation, the right posterior hepatic duct was filled with mucin. The patient had a right posterior segmentectomy. Histologically, a 2.5 0.6 0.6 cm sized mucin-producing intrahepatic cholangiocellular carcinoma was found in segment 6 of the liver. The postoperative recovery was good, and the patient has had a good social life for the last 3 years, with no evidence of tumor recurrence. In patients with a focal dilatation of the intrahepatic bile duct on CT or US with no underlying cause, an intrahepatic malignancy has to be suspected. KCI Citation Count: 0